Co-Culture Dynamics Between Lachancea Cidri and Saccharomyces Cerevisiae Impact Fermentative Aroma Profile - Cubillos-Riffo, F; Saona-Acuna, L (Elsevier B.V., 2025)
The growing demand for more aromatized and complex fermented beverages has encouraged research into non-conventional yeasts that combine bio-flavor and reproducible fermentation profiles. In this study, we explore the use of the non-conventional yeast Lachancea cidri strain CBS2950 to ferment Synthetic Wine Must in single (SWM 60 and 180 mg/L YAN) and mixed (SWM 180 mg/L YAN) fermentations with the commercial Saccharomyces cerevisiae strain EC1118. We identified that L. cidri can tolerate high ethanol concentrations (10–12 % v/v) and antimicrobial compounds commonly used in wine, such as copper sulfate and potassium metabisulphite. Interestingly, L. cidri efficiently ferments SWM, even at low nitrogen concentrations (60 mg/L YAN), generating a distinct sensory profile characterized by higher concentrations of isobutanol and ethyl ester, in contrast to that in S. cerevisiae. We analyzed the L. cidri s transcriptome after 16 h of fermentation, which remained stable when comparing 180 and 60 mg/L SWM YANs, while S. cerevisiae exhibited changes in the expression of 1,704 genes, many of them related with energy precursor metabolites, highlighting its sensitivity to low nitrogen conditions. We found that the two species could co-exist in mixed fermentation under different inoculum ratios (1:1 and 10:1) throughout the process. However, gene expression profiling revealed that L. cidri was significantly impacted by the presence of S. cerevisiae, with a more significant number of genes differentially expressed than that observed under different nitrogen conditions in single-species fermentations. The different inoculum ratios tested yielded different aroma profiles, where a higher proportion of L. cidri produced a broader range of aroma compounds. In conclusion, these results highlight the potential of L. cidri in mixed fermentations by shaping the aroma compounds in wine, offering new possibilities for fermented beverages. © 2025 The Authors